Kestabilan Model Matematika Infeksi Primer Penyakit Varicella Dan Infeksi Rekuren Penyakit Herpes Zoster Oleh Virus Varicella Zoster - Hardiyanti; Hajar; Ratianingsih, R (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2020)
Varicella and herpes zoster are two infectious skin diseases of human that caused by varicella zoster virus, where varicella disease is a primary infection that often infected younger people while herpes zoster disease is a recurrent disease that often infected older people because of reactivation of latent varicella-zoster virus. If the pain caused by herpes zoster after recurrent phase is a appeared then the condition is known as postherpetic neuralgia. This study builds a mathematical model of primary infection (varicella disease) and recurrent infection (herpes zoster disease) developed from the SIR model (Susceptible, Infected, Recovered). The human population is divided into seven subpopulations, namely susceptible, infection, recovered of varicella, herpes zoster and postherpetic neuralgia subpopulation. Stability analysis at the critical point by linearization method gives a critical point ð‘‡1 that guaranted to exist and unstable if ð›¼ ðœ‡(ð›½1+ðœ‡) ð´ , while the critical point ð‘‡1 does not have any reqruitment. Stability analysis at the endemic disease-free critical point is represented ð‘‡1 that will be unstable if ð‘‡2 exist and stable ð‘‡1 if ð‘‡2 exist. Numerical simulations by simulated to describe such temporary disease-free conditions and an endemic stable conditions.